Evaluation of the Prophylactic Effect of Amiodarone in Reducing the Incidence of Post-CABG Atrial Fibrillation - Niloofar Dadashpour; Esmaeel Moshiri; Ali Reza Kamali; Ali Reza Rostami; Majid Golestani Eraghi (Majallah-i dānishgāh-i ̒ulūm-i pizishkī-i Arāk, 2015)
Abstract Background: Atrial fibrillation (AF) is the most common complication after coronary artery bypass graft surgery (CABG). This complication causes an increase in morbidity and mortality after CABG and also increases the length of ICU stay and hospitalization. The aim of this study is to evaluate the prophylactic effect of amiodarone in reducing the incidence of post CABG atrial fibrillation. Materials and Methods: In this clinical trial study, 204 patients, candidate for elective CABG, entered the study according to inclusion and exclusion criteria, and randomly divided into two equal groups. The case group received 300 mg of intravenous amiodarone before anesthesia induction and the control group received normal saline. Incidence of AF was recorded until 24 hours after CABG. Results: The incidence of post CABG AF was 16 patients in the case group and 35 patients in the control group. Comparison of the frequency of AF between groups by Chi square analyses showed a significant difference (p=0.037) and the incidence of AF was significantly lower in the amiodarone group. Conclusion: In total, amiodarone could significantly prevent the incidence of atrial fibrillation after coronary artery bypass surgery. In this study, patients took this medication only in the first 24 hours, while in some studies, this drug has been prescribed for even 14 days.